The high-performance linear scan imaging system of terahertz Si-based blocked-impurity-band detector - Wu, Jianqing; Tao, Jia-Jia; Zhang, Chuansheng; Zhang, Haoxing; Zhang, Lei; Chen, Dong; Wang, Xiaodong (Frontiers in Electronic Materials, 2023)
Terahertz (THz) Si-based blocked-impurity-band (BIB) detector is becoming the overwhelming choice for the application in space-based instruments, airborne, and imaging systems. A high-performance linear scan imaging system based on the THz Si-based BIB detector is designed. Through the optimized design of cryogenic Dewar and suitable optical system, the imaging system reduces background stray radiation, and then improves the THz imaging performance of the detector. At the temperature of 4.2K and the bias of 2.6V, the blackbody peak responsivity of Si-based BIB detector is 23.77A/W, while the dark current is 4.72×〖10〗^(-11)A and the corresponding responsivity non-uniformity is less than 6.8%. Moreover, the experiment results show that the noise equivalent temperature difference (NETD) of the whole system reaches 10mK, and the spatial resolution reaches 50µm. This work is beneficial to the larger scale array integrated BIB imaging system.